Investigação de Casos de Sarampo no Estado de São Paulo na era Pós-Controle - Guedes Pellini, Alessandra Cristina; Ciccone, Flávia Helena; Frugis Yu, Ana Lúcia; Barbosa, Helena Aparecida (BEPA. Boletim Epidemiológico Paulista, 2005)
ver pdf